Comparison of Open MP and CUDA - Nawaz, Fazlul Kader Murshed; Chattopadhyay, Arnab; Kirthan, G J; Mane, Girish D; Savanth, Rohith N (International Journal of Computer Sciences and Engineering, 2014)
In this paper we will study the architectures of both Open Mp and CUDA architectures and make some comparisons among both in terms of basic program execution time. We will use a basic serial version of Matrix Multiplication Algorithm and modify it in terms of CUDA and Open MP and study comparatively.